Training for transformation: examining food systems courses at US land-grant universities - Hoffs, Charlie T; Chharan, Nooran; Landry, Matthew J.; Ward, Catherine P.; Oyewole, Kemi A.; Wang, May C.; Egan, Sophie; Bruce, Janine; Gardner, Christopher (Frontiers in Sustainable Food Systems, 2024)
Higher education institutions can play an essential role in preparing students to participate in movements for just and sustainable food systems change. For the past two decades, many United States land-grant universities (LGUs) have developed food systems education (FSE) courses. This study examined the extent to which FSE courses employ four capacities deemed crucial by the FSE literature: multidimensional approaches, interdisciplinarity, centering equity, and training students to take action in food systems. The syllabi of 171 undergraduate courses at 20 LGUs were obtained by contacting instructors, and their course descriptions and learning outcomes were analyzed. This subset of LGUs were identified from the membership list of the Menus of Change University Research Collaborative (MCURC), a nationwide network of colleges using campus dining halls and classrooms as living laboratories for food systems change. Most course descriptions and learning outcomes exhibited multidimensional approaches and interdisciplinarity. However, many failed to incorporate teaching content and practices that help students critically examine equity and social justice issues in food systems, or engage in transformative change. LGUs have both the resources and urgent responsibility to empower students to be part of movements to transform unjust, unsustainable food systems. The findings of this study, and an accompanying open-access syllabus website, aim to accelerate the development of FSE curricula that prepare students to change food systems.